A BTB UWB power divider with arbitrary power‐dividing ratio based on three‐slotline structure. Issue 10 (2nd August 2020) - Liu, Yaxin; Wei, Feng; Hou, Jianqiang; Shi, Xiao Wei
Abstract: In this article, a balanced‐to‐balanced (BTB) ultra‐wide band (UWB) power divider (PD) is proposed, which can realize arbitrary power‐dividing ratio (PDR) with improved transmission bandwidth flatness. The proposed PD is primarily based on microstrip/slotline (MS) transition structures and parallel‐coupled three‐slotline structure. U‐type microstrip feed lines integrated with stepped‐impedance slotline resonators are adopted at the input and output ports, which make the differential‐mode (DM) responses independent of the common‐mode (CM) ones. Meanwhile, superior DM transmission and CM suppression are achieved intrinsically, thereby simplifying the design procedure significantly. By changing the distances between the coupled three slotlines, the PDR between the output ports is controllable. In order to verify the feasibility of the proposed design method, several prototype circuits of the proposed PDs with different PDRs are simulated and a prototype circuit with the 2:1 PDR is fabricated and measured. A good agreement between the simulation and measurement results is observed.